“H1N1 influenza revisited: Our experience of the 2019 outbreak” - Hegde, Swati; Thyagaraj, Vijayashree; Prabhu, Divya (Bangladesh Journal of Medical Science, 2022)
Background: The first case of H1N1 influenza was reported in India in 2009. A decade later it continues to jeopardize India’s healthcare infrastructure. There is voluminous data available regarding the 2009 Swine flu pandemic. This study aimed to outline the clinico-laboratory profile and outcome of patients in the recent 2019 H1N1 outbreak and compare these parameters between survivors and non-survivors. Methods: This was a retrospective descriptive study of the clinico-laboratory parameters of patients hospitalized with H1N1 influenza from October 2018 to September 2019 in a tertiary care hospital in South India. Results and Discussion: Of the 121 patients included, 110 were survivors and 11 non- survivors with 9% mortality. Fever (97%) was the commonest complaint followed by cough (92%) and breathing difficulty (38%). At admission tachypnea and low saturation was common among the non-survivors and was statistically significant when compared tosurvivors. Presence of bibasal or diffuse crepitations on lung auscultation was associated with poor outcome. On chest radiographs, lower zones appeared commonly affected, and involvement of bilateral mid zone and lower zone (36.4%) was significantly higher in the non-survivors’ group. Conclusion: Our findings summarized that respiratory rate, finger pulse oximetry, and chest radiograph remain a valuable tool in identifying high risk patients. Although the mortality rate associated with H1N1 is decreasing, there is speculation aplenty whether this contagious illness has already been conquered or not. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 426-431